Research on the application of fgOTN in the new electric power system - CHEN Sunsheng; WANG Yi; LIN Mingqi; LU Shaobin; YANG Qihan; ZHENG Jian (Dianxin kexue)
With the development of new electric power systems, various emerging businesses are growing rapidly, which puts higher demands on the service granularity, bandwidth, latency, and reliability of communication transmission networks. Compared to traditional synchronous digital hierarchy (SDH) and optical transport network (OTN) technologies, fine grain optical transport network (fgOTN) technology is more suitable for the current development needs of new electric power systems. Based on this background, the standard evolution of fgOTN was described, the technical principles of fgOTN were elaborated, the application advantages of fgOTN were introduced. Finally, the adaptability of fgOTN to power system services was discussed and experimentally tested, and the test results were analyzed. The research aims to provide data references and insights for the future promotion and application of fgOTN in the electric power system.